Structural features of the mucosa of the appendix in newborns - Kravchenko, M. R. (Запорізький державний медико-фармацевтичний університет, 2025)
Aim of the study. A comprehensive histological examination of the mucosal structure of the vermiform appendix in newborns.
Keywords: тези доповідей